DNA Computing Systems Activated by Electrochemically‐triggered DNA Release from a Polymer‐brush‐modified Electrode Array. Issue 2 (5th August 2016) - Gamella, Maria; Zakharchenko, Andrey; Guz, Nataliia; Masi, Madeline; Minko, Sergiy; Kolpashchikov, Dmitry M.; Iken, Heiko; Poghossian, Arshak; Schöning, Michael J.; Katz, Evgeny
Abstract: An array of four independently wired indium tin oxide (ITO) electrodes was used for electrochemically stimulated DNA release and activation of DNA‐based Identity, AND and XOR logic gates. Single‐stranded DNA molecules were loaded on the mixed poly( N, N ‐dimethylaminoethyl methacrylate) (PDMAEMA)/poly(methacrylic acid) (PMAA) brush covalently attached to the ITO electrodes. The DNA deposition was performed at pH 5.0 when the polymer brush is positively charged due to protonation of tertiary amino groups in PDMAEMA, thus resulting in electrostatic attraction of the negatively charged DNA. By applying electrolysis at −1.0 V(vs. Ag/AgCl reference) electrochemical oxygen reduction resulted in the consumption of hydrogen ions and local pH increase near the electrode surface. The process resulted in recharging the polymer brush to the negative state due to dissociation of carboxylic groups of PMAA, thus repulsing the negatively charged DNA and releasing it from the electrode surface. The DNA release was performed in various combinations from different electrodes in the array assembly. The released DNA operated as input signals for activation of the Boolean logic gates. The developed system represents a step forward in DNA computing, combining for the first time DNA chemical processes with electronic input signals. Abstract :